2009
DOI: 10.1111/j.1748-0159.2009.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acculturation on dining‐out behavior of Koreans living in the United States – an exploratory study

Abstract: This exploratory study aimed to determine the role of acculturation on the dining‐out behavior of Koreans living in the United States. Ethnic minorities are increasing in numbers and they represent a potentially lucrative market for the foodservice industry. To target this clientele, it is essential to determine their purchasing behaviors and the factors that influence their behavior in order to design suitable marketing strategies. The results of this study showed that scores on the acculturation scale correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Chinese-Americans (e.g., Kaufman-Scarborough, 2000;Ownbey & Horridge, 1997), Chinese-Canadians (e.g., Chen, Aung, Zhou, & Kanetkar, 2005;Chia & Costigan, 2006), and Chinese-Australians (e.g., Quester, Karunaratna, & Chong, 2001). Acculturation has also received some attention in the hospitality literature, with some studies examining the effects of acculturation on the dining-out behavior of Chinese and Korean immigrants in US and Canada (Bojanic & Xu, 2006;Rajagopal, Zheng, Kang, & Lee, 2009;Yang, 2010), the restaurant selection of Korean-Americans versus that of US-born non-Koreans (Magnini, 2010), and the travel behavior of Korean-Australians (Lee & Cox, 2007). These studies found that the extent of acculturation produced significant differences among respondents in terms of their dining-out behavior, restaurant selection, and travel behavior.…”
Section: Numerous Studies Have Focused On the Acculturation Of Chines...mentioning
confidence: 99%
“…Chinese-Americans (e.g., Kaufman-Scarborough, 2000;Ownbey & Horridge, 1997), Chinese-Canadians (e.g., Chen, Aung, Zhou, & Kanetkar, 2005;Chia & Costigan, 2006), and Chinese-Australians (e.g., Quester, Karunaratna, & Chong, 2001). Acculturation has also received some attention in the hospitality literature, with some studies examining the effects of acculturation on the dining-out behavior of Chinese and Korean immigrants in US and Canada (Bojanic & Xu, 2006;Rajagopal, Zheng, Kang, & Lee, 2009;Yang, 2010), the restaurant selection of Korean-Americans versus that of US-born non-Koreans (Magnini, 2010), and the travel behavior of Korean-Australians (Lee & Cox, 2007). These studies found that the extent of acculturation produced significant differences among respondents in terms of their dining-out behavior, restaurant selection, and travel behavior.…”
Section: Numerous Studies Have Focused On the Acculturation Of Chines...mentioning
confidence: 99%
“…The topic of acculturation has received some attention in both the tourism and hospitality context. From the consumer perspective, research has examined the impact of acculturation on dining-out behavior of Chinese and Korean immigrants in Canada and the US respectively (Yang, 2010;Bojanic & Xu, 2006;Rajagopal, Zheng, Kang & Lee, 2009), restaurant selection of Korean-Americans versus US born non-Koreans (Magnini, 2010) and travel behavior of Korean immigrants in Australia (Lee & Cox, 2007), with all these studies pointing to significant differences in respondents depending on the extent of their acculturation. A related stream of research focused on acculturation of Chinese immigrants, including that of Chinese-Americans (e.g., Kaufman-Scarborough 2000), Chinese-Canadians (e.g., Chen, Aung, Zhou & Kanetkar, 2005) and Australian-Chinese (e.g., Quester, Karunaratna, & Chong, 2001), with contexts of these studies ranging from food consumption to consumption of durable goods.…”
Section: Acculturation Theorymentioning
confidence: 99%
“…Numerous studies have focused on acculturation of Chinese consumers in the United States (e.g., Kaufman-Scarborough 2000; Ownbey and Horridge 1997), Canada (e.g., Chen et al 2005; Chia and Costigan 2006), and Australia (e.g., Quester and Chong 2001; Quester, Karunaratna, and Chong 2001). Acculturation has also been considered in dining-out behavior of Chinese immigrants in the United States and Koreans in Canada (Bojanic and Xu 2006; Rajagopal et al 2009; Yang 2010), restaurant selection of Korean Americans versus U.S. natives (Magnini 2010), and travel behavior of Korean immigrants in Australia (S. H. Lee and Cox 2007).…”
Section: Literature Reviewmentioning
confidence: 99%